THE INFLUENCE OF USING WEBLOG-BASED ECONOMIC LEARNING MODULES ON PHASE F STUDENTS' LEARNING OUTCOMES - Tasya Refjuandani; Sri Arita (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2025)
This study was motivated by the learning outcomes of national income material at SMAN 1 Pancung Soal still looks low because there are still many students who have difficulty in understanding the material and students are less active in the learning process. This study aims to analyze the effect of weblog-based learning modules on the learning outcomes of phase F students of SMAN 1 Pancung Soal. This study used a pseudo-experimental method with a nonequivalent control group design. The population consisted of all phase F students in the economics class of the 2024/2025 school year with sampling using purposive sampling technique. The results of media expert validation obtained a percentage of 96% with very valid criteria. The research data shows that the hypothesis is accepted. The results of the man whitney test at a significance level of 0.00 obtained Sig <0.05 which states the effect of using a weblog-based economic module is effective in improving student learning outcomes.